Analysis of Islamic Higher Education Quality Mapping Based on Student Service Satisfaction Using Multidimensional Scaling Method - Hasanah, Nur; Prihono, Eko Wahyunanto; Retnawati, Heri; Fajaruddin, Syarief; Wulansari, Andhita Dessy; Muhtarom, Taufik (IAIN Ponorogo, 2022)
This study aims to analyze the mapping of the quality of Islamic higher education based on the similarity of student service satisfaction. This study used ex-post-facto research with an explorative. It employed a descriptive design. The subjects consisted of students from various study programs at the FETT, the SII Ambon. Data were collected through student satisfaction questionnaires. Data analysis was performed using Multidimensional Scaling. The results showed similarities in mapping the quality of Islamic higher education based on student service satisfaction from 6 study programs. It calculated the closest Euclidean distance between objects located in Biology Education and Islamic Education study programs or vice versa, where the proximity is 0.233. It indicates that the quality of education in student service satisfaction between Biology Education and Islamic Education study programs has the highest similarity compared to other study programs. The output of the MDS analysis obtained a stress value of 0.03671 (3.67%) and R2 of 0.99606. It represents an acceptable spatial map (R2 ≥ 0.6).